Peraturan Bupati Tentang Optimalisasi Kandungan Lokal dalam Kegiatan Industri Migas di Kabupaten Bojonegoro - Rupiarsieh, . (REFORMASI, 2023)
Bojonegoro Regency is one of the major oil and gas producing regions in Indonesia. On the one hand, increasing regional income. On the other hand, it has the potential to cause social unrest, especially in producing villages. Bojonegoro Regent Regulation Number 48 of 2011 concerning Local Optimization in Oil and Gas Industry Activities in Bojonegoro Regency is expected to be able to suppress the jealousy of local people in exploration activities. This study aims to evaluate the policy of Perbup No 48 of 2011, which is measured by six indicators from William Dunn's evaluation theory. Namely, effectiveness, efficiency, accuracy, adequacy, equity/equality, and responsiveness. The study used a descriptive qualitative research type. The research location is in Ngampel Village, Kapas District. Data collection techniques in the form of observation, in-depth interviews and documentation studies. The results showed that Perbup Number 48 of 2011 went through a process of study/discussion and encouragement from various parties. This Perbup was born after the issuance of Regional Regulation No. 23 of 2011. Thus, it is seen as more efficient in providing a form of partiality to local people, even though it has not been fully effective and efficient.AbstrakKabupaten Bojonegoro merupakan salah satu daerah penghasil migas besar di Indonesia. Di satu sisi, meningkatkan pendapatan daerah. Di sisi lain berpotensi menimbulkan gejolak sosial, terutama di desa penghasil. Peraturan Bupati Bojonegoro Nomor 48 Tahun 2011 tentang Optimalisasi Lokal dalam Kegiatan Industri Migas di Kabupaten Bojonegoro diharapkan mampu menekan kecemburuan masyarakat lokal dalam kegiatan eksplorasi. Studi ini bertujuan mengevaluasi kebijakan Perbup No 48 Tahun 2011, yang diukur dengan enam indikator dari teori evaluasi William Dunn. Yakni, efektivitas, efisiensi, ketepatan, kecukupan, pemerataan/kesamaan, dan responsivitas. Studi menggunakan penelitian jenis penelitian kualitatif deskriptif. Lokasi penelitian di Desa Ngampel, Kecamatan Kapas. Teknik pengumpulan data berupa observasi, wawancara mendalam dan studi dokumentasi. Hasil penelitian menunjukkan, Perbup Nomor 48 Tahun 2011 melalui proses kajian/diskursus dan dorongan berbagai pihak. Perbup ini lahir setelah sebelumnya terbit Perda Nomor 23 tahun 2011. Sehingga, dipandang lebih efisien dalam memberikan bentuk pemihakan kepada lokal, meski belum sepenuhnya berjalan efektif dan efisien.